Biomechanics Assessment of Kinematic Parameters of Low-Sprint Start in High-Performance Athletes Using Three Dimensional Motion Capture System - Gonzalez Macias, Mirvana Elizabeth; Villa Angulo, Carlos; Arrayales Millan, Emilio Manuel; Keys Gonzalez, Karla Raquel (Revista Mexicana de Ingenieria Biomedica, 2022)
In a sprint start, the athlete takes up a position with their hands just behind a line, arms vertical, feet generally placed about a shoe length apart, and the hips rising above the line of the head. Mistakes in this position influence the execution of the low-sprint start, and can drastically influence the initial running speed and acceleration achieved by the athlete. Common mistakes occur due to the misconception that athletes must also lean forward, bringing the shoulders ahead of their hands and putting pressure on them. A standard approach to identify sprint start mistakes is to use a stick or weighted string to drop down from the shoulders. The effective implementation of this approach depends on the coach’s experience and remains a significant challenge. In this study, a three-dimensional motion capture system with the Vicon® Plug-in-Gait model was used to characterize the kinematic parameters that influence the execution of low-sprint start in six high-performance athletes. The main kinematic parameters are reaction time, stride length, and stride time. The obtained results demonstrate the potential utility of a three-dimensional motion capture system to assess the kinematic parameters of low-sprint start in high-performance athletes.